The Role of the Pre-B Cell Receptor in B Cell Development, Repertoire Selection, and Tolerance - Winkler, Thomas H.; Mårtensson, Inga-Lill (Frontiers in Immunology, 2018)
Around four decades ago, it had been observed that there were cell lines as well as cells in the fetal liver that expressed antibody  heavy (H) chains in the apparent absence of bona fide light chains. It was thus possible that these cells expressed another molecule(s), that assembled with H chains. The ensuing studies led to the discovery of the pre-B cell receptor (pre-BCR), which is assembled from Ig H and surrogate light (SL) chains, together with the signaling molecules Ig and . It is expressed on a fraction of pro-B (pre-BI) cells and most large pre-B(II) cells, and has been implicated in IgH chain allelic exclusion and down-regulation of the recombination machinery, assessment of the expressed H chains and shaping the IgH repertoire, transition from the pro-B to pre-B stage, pre-B cell expansion and cessation.